2021
DOI: 10.33369/pendipa.6.1.26-34
|View full text |Cite
|
Sign up to set email alerts
|

Development of Articulate Storyline-based Dynamic Fluid Learning Media For Grade XI High School Students

Abstract: Articulate Storyline (AS) is a learning media creation software that presents materials with storylines. The presence of added characters makes the learning media more interactive and more immersed in the story presented. The use of characters is expected to appeal to students learning. The topic used in the learning media developed is Dynamic Fluid. The purpose of this research is to design a physics learning medium that implements Dynamic Fluid theories into a storyline using an Articulate Storyline. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 1 publication
2
5
0
7
Order By: Relevance
“…(Rohmah & Bukhori, 2020) Also, learning media using articulate storyline 3 can be used as a learning resource and as a supporting medium for distance learning. This is in line with previous research conducted by (Fatikhah & Anggaryani, 2022) which aims to find out the effectiveness of the application of articulate storyline-based learning objects "Very Effective" and very feasible to use and significant to students' cognitive abilities, the improvement of cognitive abilities is quite effective, and the student response category is very positive. (Hadza et al, 2020) suggest that it was found that teachers use storyline articulate-based object media for classroom learning very effectively used to improve student understanding, especially in abstract materials.…”
Section: Effectiveness Of Articulate Storyline Economic Learning Medi...supporting
confidence: 89%
See 1 more Smart Citation
“…(Rohmah & Bukhori, 2020) Also, learning media using articulate storyline 3 can be used as a learning resource and as a supporting medium for distance learning. This is in line with previous research conducted by (Fatikhah & Anggaryani, 2022) which aims to find out the effectiveness of the application of articulate storyline-based learning objects "Very Effective" and very feasible to use and significant to students' cognitive abilities, the improvement of cognitive abilities is quite effective, and the student response category is very positive. (Hadza et al, 2020) suggest that it was found that teachers use storyline articulate-based object media for classroom learning very effectively used to improve student understanding, especially in abstract materials.…”
Section: Effectiveness Of Articulate Storyline Economic Learning Medi...supporting
confidence: 89%
“…The feasibility of the media used can be seen from the ease and practicality of use by students. In addition to assisting teachers in the delivery of economic learning materials (Fatikhah & Anggaryani, 2022). This is in line with the opinions of experts who say that articulate storyline is one of the software creation media that has many advantages and is easy to learn, so the selection of storyline articulate in making learning media is one of the most interesting things to develop (Yoana, 2016).…”
Section: Feasibility Of Articulate Economic Learning Media Storyline ...mentioning
confidence: 61%
“…A. P. Sari & Afandi, 2021). Recommendations that can be considered are the benefits derived from the interactive picture and picture learning media based on articulate storylines in the learning process of which can be made yourself because the application of the articulate storyline is easy to understand (Fatikhah & Anggaryani, 2022;Gardner et al, 2020;Sindu et al, 2020). Various files can be included in photos, videos, animations, or audio.…”
Section: Ranksmentioning
confidence: 99%
“…Media pembelajaran menggunakan articulate storyline dinyatakan sangat layak sesuai dengan penelitian Purnama & Asto (2014) yang menunjukkan media interaktif memanfaatkan articulate storyline sangat relevan diterapkan karena materi dijelaskan secara berurutan dengan dukungan ilustrasi dan kalimat yang jelas sehingga mudah dipahami. Media sangat layak digunakan dalam kegiatan pembelajaran karena media memiliki memiliki keakuratan isi, contoh dan animasi serta tampilan yang menarik dan interaktif sehingga tidak membosankan (Nurmala dkk., 2021) dan media mampu mengomunikasikan materi dengan baik secara visual sehingga mampu menarik perhatian siswa dalam pembelajaran (Fatikhah & Anggaryani, 2022) dimana media yang menarik akan menumbuhkan inspirasi belajar siswa (Arsyad, 2015) karena adanya perbedaan tingkat motivasi siswa menyebabkan penggunaan media berupa video, gambar dan animasi lebih optimal dalam menarik perhatian siswa (Rafmana dkk., 2018) sehingga media pembelajaran dapat menjelaskan dan memudahkan pemahaman pada gagasan yang kurang jelas, maya atau bias (Daryanto, 2016) maka dari itu, media pembelajaran interaktif menggunakan articulate storyline sangat layak diuji cobakan dan diterapkan dalam pembelajaran. Berdasarkan tabel 6 diketahui bahwa ratarata nilai pretest dari 35 siswa sebesar 48 dan ratarata nilai posttest sebesar 63 dengan nilai maksimum sebesar 75 karena setiap jawaban benar bernilai 5.…”
Section: A Hasil Validasi Ahli Mediaunclassified
“…Bagan 1 Peningkatan Hasil Belajar Siswa Media pembelajaran berbasis articulate stroryline sangat efektif dan membuat pembelajaran berjalan maksimal karena mampu meningkatkan nilai belajar siswa sehingga nilai yang didapat dinyatakan tuntas (Fatikhah & Anggaryani, 2022). Penelitian yang dilakukan Hidayati (2022) juga menunjukkan hasil yang positif dimana software articulate storyline efektif menaikkan perolehan nilai siswa karena terdapat peningkatan nilai posttest sedangkan pada penelitian Sari & Susanti (2016) keefektifan media berbasis articulate storyline mendapatkan nilai 79,16% menunjukkan alat bantu penyampaian materi yang menimbulkan interaksi aktif dinyatakan efektif karena mampu membuat kegiatan pembelajaran menjadi lebih efektif.…”
Section: Keefektifan Media Interaktif Menggunakanunclassified